Interest margins determinants of Czech banks - Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2009)
We examine the determinants of interest rate margins of Czech banks employing bank-level dataset at the quarterly frequency in 2000-2006. Our main results are as follows. We find that more efficient banks exhibit lower margins and there is no evidence that the banks with lower margins would compensate themselves with higher fees. Price stability contributes to lower margins. There are some economies of scale, as larger banks tend to charge lower margins. Higher capital adequacy is associated with lower margins contributing to the banking stability. Overall, the results indicate that the determinants of interest rate margins of Czech banks are largely similar to those reported in other studies for developed countries.
Keywords: G21; D40; P27; 330; commercial banks; interest rate margins; bank efficiency; Zinsspanne; Bank; Tschechische Republik